2019
DOI: 10.21470/1678-9741-2018-0312
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High-Dose Vitamin C on Biochemical Markers of Myocardial Injury in Coronary Artery Bypass Surgery

Abstract: ObjectiveTo evaluate the effect of high-dose vitamin C on cardiac reperfusion injury and plasma levels of creatine kinase-muscle/brain (CK-MB), troponin I, and lactate dehydrogenase (LDH) in patients undergoing coronary artery bypass grafting (CABG).MethodsThis is a double-blind randomized clinical trial study. Fifty patients (50-80 years old) who had CABG surgery were selected. The intervention group received 5 g of intravenous vitamin C before anesthesia induction and 5 g of vitamin C in cardioplegic solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…The overall findings here are consistent with the data on the cardioprotective effect of VC from clinical trials of coronary reperfusion surgery patients. Two of these clinical trials showed that administration of VC before coronary artery bypass grafting (CABG) surgery significantly improved LVEF [ 56 , 57 ]. Similar to the PCI trials presented here, VC was given via iv infusion before CABG and was found to reduce cardiac injury [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall findings here are consistent with the data on the cardioprotective effect of VC from clinical trials of coronary reperfusion surgery patients. Two of these clinical trials showed that administration of VC before coronary artery bypass grafting (CABG) surgery significantly improved LVEF [ 56 , 57 ]. Similar to the PCI trials presented here, VC was given via iv infusion before CABG and was found to reduce cardiac injury [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two of these clinical trials showed that administration of VC before coronary artery bypass grafting (CABG) surgery significantly improved LVEF [ 56 , 57 ]. Similar to the PCI trials presented here, VC was given via iv infusion before CABG and was found to reduce cardiac injury [ 56 , 57 ]. Three systematic reviews with meta-analysis have summarized the benefit of VC for CABG and cardiac surgery patients [ 45 , 46 , 47 , 48 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients had lower oxidative damage, lower myocardial damage, better postoperative cardiac index and shorter hospital stay. Emadi et al (22) observed improved ventricular function 72 h after surgery and reduced length of intensive care unit stay. Two other studies showed increased levels of plasma malondialdehyde (MDA), a marker of lipid peroxidation, after CPB (10,30).…”
Section: Cardiopulmonary Bypass and Cardiac Surgerymentioning
confidence: 97%
“…In one clinical study, vitamin C treatment could increase the beneficial effects of ß-blocker against AF in patients undergoing CABG [ 276 ]. However, some clinical studies were not able to find significant effects on heart enzymes [ 267 , 277 ], inflammation markers [ 278 ] or AF [ 266 ]. In animal models, beneficial effects of vitamin C supplemented preservation solution in terms of graft protection have been observed [ 279 ].…”
Section: Vitamin Cmentioning
confidence: 99%
“…Transplantation [260] -Varying concentrations AA [260] blood circulation improved hyperfibrinolysis by improvement of clot rigidity [260] Vitamin C Heart CABG [265,266,[274][275][276][277][278] percutaneous coronary intervention [269,270] cardiac surgery [267,273] PAD [271] valve replacement surgery [274,278] pump circulation during surgery [265] i.v. [266,267,270,271,273,274,277] p.o.…”
Section: Livermentioning
confidence: 99%